Assessment of neck disability index in people with bruxism - Trukawka, Kinga; Gębska, Magdalena; Mikołajczyk-Kocięcka, Anna; Weber-Nowakowska, Katarzyna; Żyżniewska-Banaszak, Ewelina (Journal of Education, Health and Sport, 2022)
Aim: Assessment of neck disability index in people with bruxism. Material and Methods: The study was conducted on a group of 40 subjects of both sexes, in the age range of 18 to 38 years old, with diagnosed bruxism according to Panek (B2, B3). The control group consisted of the same number of subjects in the same age range without bruxism. The research tool was the standardized neck spine disability index (NDI). The scale consists of an examination date and a follow-up after time and 10 questions related to: pain intensity, daily activities, lifting, reading, headaches, concentration, working, driving, sleeping and recreation. Results: Individuals with bruxism are more likely to have higher rates of neck disability index. The analyses conducted showed that individuals diagnosed with bruxism achieved higher levels of pain for almost all factors on the NDI scale. The study found that significantly higher difficulty and pain intensity was present for almost all aspects among those aged 25-31 years, those with a university education, and those who were employed. Conclusion: The biomechanical connections between the stomatognathic system and the cervical spine indicate the need for functional assessment of the cervical spine in individuals with bruxism.